IMPLIKASI BANTUAN OPERASIONAL SEKOLAH (BOS) BUKU TERHADAP KREATIVITAS GURU MENULIS BUKU MODUL - Isharijadi, Isharijadi (Jurnal Pendidikan, 2008)
ThisÂ researchÂ servesÂ an analysisÂ as to empiricallyÂ Â explainÂ the implementationÂ Â Â of School Operational GrantÂ (BOS)Â for books from government andÂ its relevanceÂ Â towardsÂ the teachers creativeness in writingÂ Â booksÂ andÂ modules.Â Â SchoolÂ OperationalÂ Â Grant Â for booksÂ is intendedÂ Â Â toÂ easeÂ Â studentsâ parentsÂ Â inÂ providingÂ Â Â booksÂ Â forÂ their children.Teachers, as the front-liners for the students learning development, are attempted to creatively provide theÂ sufficient learningÂ resources, one of which is done byÂ arrangingÂ Â Â subject modules.Â Â Â TheÂ Â teachersÂ Â Â areÂ obligedÂ Â forÂ arrangementÂ Â Â ofÂ learning modules,Â Â becauseÂ throughÂ the modulesÂ they can renderÂ creativeness and materialÂ Â developmentÂ Â for studentsÂ basedÂ on the developmentÂ Â of theÂ marketÂ shareÂ and lack of teachers works.UnderÂ empiricalÂ observationÂ done by the researcher,Â it is found that the School OperationalÂ Grant for books arises dilemma for teachers and publicÂ in terms thatÂ 1) teachersÂ face difficultiesÂ to distributeÂ their works/modulesÂ Â in substitutionÂ for books from BOS, 2) the demandÂ for teachersÂ Â Â modulesÂ Â and booksÂ becomesÂ Â studentsÂ Â parentsÂ burden,Â 3) the distributionÂ Â of the grant books which needs veryÂ strict supervision fromÂ the authority.Key terms:Â BOS for books,Â teachersÂ Â creativeness